The Influence of Digital Financial Literacy on Saving Behavior Among Gen Z in Indonesia - Saidah Mubarokah; Pristin Prima Sari; Ratih Kusumawardhani (Indonesian Journal of Economics, Business, Accounting, and Management (IJEBAM), 2024)
This research aims to determine the influence of digital financial literacy on saving behavior of generation z in Indonesia. The number of respondents of this research was 312 people, both from Java and non-Java. We carry out data processing using SmartPLS 3.0 software. In this research, we found that there is a positive and significant relationship between digital financial literacy and saving behavior of generation z in Indonesia. This means that the better a person's level of digital financial literacy, the better their financial behavior in terms of saving. There are still limitations to this research, namely that there are still provinces in Indonesia that have not participated in this research, so we suggest that the future research will be able to obtain respondents from all provinces in Indonesia